Dividend yields and business confidence as predictors of returns on the London Stock Exchange - Fielding, John Anthony (Cranfield University, 1996)
This thesis examines the relationship between future returns and dividend yields on the London Stock Exchange for the period 1966 to 1993. An additional set of explanatory variables is introduced in the form of the Confederation of British Industries, Industrial Trends Survey data. A significant relationship was found between dividend yields and future returns when regression statistics were generated by ordinary least squares. The relationship was shown, however, to be attributable only to the period from 1966 to 1980 and in particular to the turbulent era from 1973 to 1975. When allowance was made for the effect of a lagged regressor by use of the Goetzmann and Jorion (1993) simulation model, no significant relationship between dividend yields and future returns for the entire sample period was found. Ordinary Least Squares estimation of regressions of future returns on the Confederation of British Industries surveys of Business Opinion showed only a modest relationship. This was considerably weakened when the regression coefficients were estimated by randomisation. In common with Dividend Yields the relationship was entirely a feature of the 1966 to 1980 period. The evidence provided by this study does not enable the refutation of the semi-strong form of market efficiency.